Analyzing social cohesion in open spaces of multiethnic poor neighborhoods: a grounded theory study - Salimi, Marziyeh; Foroutan, Manouchehr; Naghdi, Asadollah (Journal of Architecture and Urbanism, 2019)
During the past two decades, economic crises and climate change have triggered mass migrations from rural areas to big cities and metropolises. Considering that the destination cities often lack the required capacity to systematically accommodate these newcomers, immigrants settle in unofficially on city margins. Since these immigrants have different ethnicities, the informal settlements constructed by them turn into multiethnic informal Settlements in which development of proper social ties becomes impeded. As a result, social cohesion is weakened and eventually ceases to exist among the residents in open community spaces. In this regard, the present study aims to analyze this process and the effects of multiethnicity on social cohesion in the open community spaces of poor urban areas and the role of environmental factors in this mechanism. The Hesar Imam Khomeini neighborhood, which is located in Hamadan Province and has a rural core, has given shelter to Lurish, Kurdish, Turkish and Persian-speaking immigrants during recent years, which makes it a suitable sample for study. Because of the existing limitations and in order to achieve the goal of the study, the grounded theory was used to conduct the research. In-depth interview was carried out on sixteen residents of the neighborhood, four individuals from each ethnicity. After coding the interviews using the theory, a grounded model of the study was formed. The results indicate that multiethnicity has negatively affected behavior settings, vibrancy and consequently social cohesion in the open community spaces of the area of study through the three factors of “different expectations from neighborhood space”, “different time of attendance in open spaces” and “different residence size”. It can be proposed that “creating spatial shared values” is one of the most effective strategies which can be used for narrowing gaps and increasing social cohesion in multiethnic neighborhoods.